Antenatal care practices among the women with children under five-years of age in an eastern Nepal village: A cross sectional study - Subedi, Laxmi; Sah, Ram Bilakshan; Regmi, Mohan Chandra (Journal of Kathmandu Medical College, 2017)
Background: Antenatal care has proven to be an effective way to reduce maternal mortality and save the life of newborn. Nepal also follows the World Health Organization’s recommendations of initiation of four antenatal care visits that has helped in decreasing the maternal mortality of the country. Still, the country has to do a lot in improving the antenatal care provision.Objective: The objective of this study was to find out the antenatal care practices among the women with children less than five years of age in a district of eastern Nepal.Methods: A descriptive cross-sectional study was conducted among residents of Aurabani village of Sunsari district. Non probability convenient sampling technique was used to collect data from 15th January to 30th January, 2015. Data of 100 women having children less than five years of age were collected and analyzed in descriptive and inferential ways.Results: Women with nuclear family are more likely to have antenatal care visits (73.8%) compared to women with joint family (66.7%). The study showed that attendance of antenatal care visits among the educated women was higher (71.8%) than those illiterate (66.7%). In the study, 84.8% of women of primi-gravida completed antenatal care visit which was significantly higher than women with multi gravida (59.3%) (p